Kolaborasi Berbasis IPTEK untuk Pembangunan Masyarakat Desa Godog Kecamatan Karangpawitan Kabupaten Garut - Melinda, Linda Daniati; Jajang Burhanudin; Anna Noviana (Darma Abdi Karya, 2023)
The 2023 LP3I Polytechnic Community Service activities carried out by Field Supervisors and students were held in Godog Village, Karangpawitan District, Garut Regency from 15 July - to 19 August 2023. Some of the problems that exist in Godog Village as a result of observations with local community leaders are: interaction between residents in the housing circle has not been well created, Godog Village residents are not aware of the importance of digitalization, and students in the Karangpawitan area still consider it not important to continue their education. Researchers used the Service Learning (SL) approach. SL is intended to integrate learning into community service activities. This service program aims to have a beneficial impact on the development of the area where it is implemented.